A Planar-Chiral Pillar[5]arene-Based Monophosphine Ligand with Induced Chirality at the Biaryl Axis - Nagata, Yuuya; Shimada, Yasuo; Nishikawa, Tsuyoshi; Takeda, Ryohei; Uno, Makoto; Ogoshi, Tomoki; Suginome, Michinori (Synlett, 2018)
A planar-chiral pillar[5]arene with cyclohexylmethoxy side chains and a pendant diphenylphosphine was prepared and used as a chiral ligand in asymmetric reactions. Chirality transfer from the planar-chiral pillar[5]arene scaffold to the chiral biaryl moiety was demonstrated by circular dichroism (CD) spectroscopy, single-crystal X-ray diffraction analysis, and asymmetric catalysis.
Keywords: pillar[5]arene; planar chirality; circular dichroism; chiral ligand